2020
DOI: 10.1007/s10557-020-07086-7
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Cardioprotective Effect of MitoGamide in the Diabetic Heart

Abstract: Purpose HFpEF (heart failure with preserved ejection fraction) is a major consequence of diabetic cardiomyopathy with no effective treatments. Here, we have characterized Akita mice as a preclinical model of HFpEF and used it to confirm the therapeutic efficacy of the mitochondria-targeted dicarbonyl scavenger, MitoGamide. Methods and Results A longitudinal echocardiographic analysis confirmed that Akita mice develop diastolic dysfunction with reduced E peak velocity, E/A ratio and extended isovolumetric rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The explored approaches include the use of superoxide dismutases and relative mimetics [ 103 , [114] , [115] , [116] ], the mitochondrially targeted antioxidant MitoQ [ 102 , 117 , 118 ], N-acetylcysteine [ 119 , 120 ], metformin [ 121 , 122 ], which also acts as a weak complex I inhibitor [ 123 ], and the administration of natural compounds, such as vitamin C [ 124 ]. In addition, recent studies have reported the cardioprotective potential of a mitochondrially targeted MGO and GO scavenger, referred to as MitoGamide, which might be a future promising candidate for IR therapy [ 125 , 126 ]. Besides these compounds in the antioxidant field, interesting insights have been obtained from studies involving the multifaceted protein DJ-1, which is gaining more and more attention as a protective player in response to IR injury.…”
Section: Pathophysiology Of Ir Injurymentioning
confidence: 99%
“…The explored approaches include the use of superoxide dismutases and relative mimetics [ 103 , [114] , [115] , [116] ], the mitochondrially targeted antioxidant MitoQ [ 102 , 117 , 118 ], N-acetylcysteine [ 119 , 120 ], metformin [ 121 , 122 ], which also acts as a weak complex I inhibitor [ 123 ], and the administration of natural compounds, such as vitamin C [ 124 ]. In addition, recent studies have reported the cardioprotective potential of a mitochondrially targeted MGO and GO scavenger, referred to as MitoGamide, which might be a future promising candidate for IR therapy [ 125 , 126 ]. Besides these compounds in the antioxidant field, interesting insights have been obtained from studies involving the multifaceted protein DJ-1, which is gaining more and more attention as a protective player in response to IR injury.…”
Section: Pathophysiology Of Ir Injurymentioning
confidence: 99%
“…MitoGamide ( Figure 1 a) was synthesized as previously described [ 30 ]. At 6 weeks of age, male mice of both genotypes were randomly assigned to receive either vehicle (10% ethanol in water) or MitoGamide (10 mg/kg) by daily oral gavage ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…MitoGamide (10 mg/kg) was given to mice ( n = 3) by oral gavage, then its contents in the heart, liver, and kidney were measured by LC-MS/MS, as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several naturally occurring substances, including co-enzyme Q, idebenone, and dimethylglycine, have been demonstrated to improve mitochondrial ATP synthesis in patients with various mitochondrial disorders [ 156 , 157 , 158 , 159 ]. Additional compounds have been generated to reduce ROS production or directly scavenge ROS to reduce the burden of oxidative stress associated with mitochondrial pathologies [ 160 , 161 , 162 , 163 , 164 ]. Given that oxidative stress and impairment of oxidative phosphorylation are clearly present in the human PAD skeletal muscle, mitochondrial-targeted therapies may be an untapped area of therapeutic investigation.…”
Section: Therapeutic Targeting Of Mitochondria: the Future Is Brigmentioning
confidence: 99%